Evaluation of Crestal Bone Resorption around Dental Implants In Flapped and Flapless Surgical Techniques Depending on Cone Beam CT Scan (Comparative Study) - Mustafa Abdul Hussein Al Najjar (Journal of Global Pharma Technology, 2016)
around the implants. Some initial loss of bone around dental implants is generally expected. There is reason to believe that reflecting a mucoperiosteal flap promotes crestal bone loss in the initial phase after an implant has been inserted. The surgical placement of a dental implant fixture is constantly changing and in recent years, there has been some interest in developing techniques that minimize the invasive nature of the procedure, with flapless implant surgery being advocated. The purpose of this study was to compare the radiographic level of the peri- implant bone after implant placement between traditional flapped surgery and flapless approach depending on CBCT during 24 weeks healing period. Materials and Methods: A total of 25 Iraqi patients with 46 implants aged 20-60 years .Were randomized into two groups: control group which involved 27 implants inserted by conventional flapped surgical approach and study group which involved 19 implants inserted by flapless surgical approach. The bone level was measured by CBCT for each implant at buccal and palata/ lingual sides at two times, immediately after implant placement (base line data), and after 24 weeks healing period. Results: There was no significant difference between study (flapless) and control (flapped) groups in the mean of total crestal bone resorption for buccal and palatal sides. Conclusions: Bone resoption around dental implants placed with conventional flap surgery compared to flapless surgery does not seem to be influenced during the healing period before implant loading.